Life and Work of Prague Master Simon of Tišnov - Dobiáš, Karel (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The Bohemian Reformation is a widely researched topic. However, not enough attention is given to all participants during the course events. The aim of this article is to introduce the life and literary work of the little-known University of Prague Master, Simon of Tišnov (ca. 1370–1432), a medieval scholar with roots in the Moravian town called Tišnov, a defender of John Wycliffe’s philosophy, an ardent supporter of the Bohemian reformation movement and, eventually, an objector, or rather an opponent, of those who followed the teachings of John Wycliffe and John Hus. The article is focused on Simon’s very first publication, viz. the Defensio of John Wycliffe’s treatise De probationibus propositionum which is also known under the title Logicae continuatio.